2021
DOI: 10.17582/journal.aavs/2021/9.7.1095.1112
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate and Rosemary Leaf Meal Inclusion in Broiler Diet: Effects on Gut Micro-Floral, Growth Performance, Ileum, Jejunum and Duodenal Histological Traits

Abstract: The gut histological traits, gut micro-flora and growth parameters of boiler birds fed different inclusion levels of sodium butyrate and rosemary leaf meal was investigated. A total of 320 one-day "Arbor acre strain" broiler chicks were allotted to 10 dietary treatments with 4 replicates of 8 birds each. The treatments includes : T1 = Basal diet (BD: Negative control); T2 = BD + 1g/Kg diet of Oxytetracycline (positive control); T3 = BD+2g sodium butyrate (SB) /kg diet; T4 = BD+4g SB/Kg diet; T5 = BD + 2.5g ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…(2018); Lan et al . (2020) and Ogwuegbu et al . (2021) who discovered that adding SB and RL to the basal diet had a positive impact on carcass characteristics of broiler chickens.…”
Section: Discussionmentioning
confidence: 96%
“…(2018); Lan et al . (2020) and Ogwuegbu et al . (2021) who discovered that adding SB and RL to the basal diet had a positive impact on carcass characteristics of broiler chickens.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Feshanghchi et al (2022) found that dietary Spirulina at a level of 1% decreased cecal E. coli counts in broiler chickens given aflatoxin-contaminated diets. Moreover, earlier literature recorded that rosemary extract had the potential to reconstruct the gut microbiota in mice ( He et al, 2022 ), and rosemary leaf meal can increase Lactobacillus count but decrease E. coli and Salmonella populations in broilers ( Ogwuegbu et al, 2021 ). Mathlouthi et al (2012) reported that REO had numerous antimicrobial effects on harmful pathogens and even had the same effect as avilamycin when included in broiler rations.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbial homeostasis was required for the development and maturation of the animals, which affected a wide range of physiology aspects, including growth performance, production performance, nutrient digestibility, immune function, and antioxidative capacity ( Sommer and Bäckhed, 2013 ; Fathima et al, 2022 ). Previous literature reported that RE had the potential to reshape the gut microflora in mice under stressed conditions ( Guo et al, 2018 ; He et al, 2022 ), and rosemary leaf meal could increase the population of Lactobacillus but reduce the population of E. coli and Salmonella ( Ogwuegbu et al, 2021 ). However, in the present study, 750 mg/kg dietary RE did not change the α or β diversity of the gut microflora in broilers ( P >0.05).…”
Section: Discussionmentioning
confidence: 99%